Wounds and words : childhood and family trauma in romantic and postmodern fiction - Schönfelder, Christa (Lettre (Transcript (Firm)), 2013)
Trauma has become a hotly contested topic in literary studies. But interest in trauma is not new; its roots extend to the Romantic period, when novelists and the first psychiatrists influenced each others' investigations of the "wounded mind". This book looks back to these early attempts to understand trauma, reading a selection of Romantic novels in dialogue with Romantic and contemporary psychiatry. It then carries that dialogue forward to postmodern fiction, examining further how empirical approaches can deepen our theorizations of trauma. Within an interdisciplinary framework, this study reveals fresh insights into the poetics, politics, and ethics of trauma fiction.